Capacity Teacher’s Strengthening in Writing and Publishing Scientific Research Articles - Enggal Mursalin; Aria Bayu Setiaji (MANGENTE: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
Abstract. The implementation of this Community Service (PkM) activity aims to improve the ability of teachers to write scientific research articles. Furthermore, the articles are expected to be published in scientific journals. Through this PkM activity, teachers are expected to be able to, 1) have basic knowledge of the steps for compiling scientific articles on research results properly and correctly; 2) search for scientific journals in order to publish scientific articles; and 3) knowing how to publish scientific articles in several scientific journals at the IAIN Ambon Journal House. The training participants were 20 teachers at Madrasah Tsanawiyah (MTs) Al-Ansor Ambon City with various educational backgrounds. The materials presented during the training were 1) tips and tricks for compiling scientific research articles, 2) strategies for selecting nationally accredited scientific journals that are in accordance with scientific articles, and 3) the stages of submitting scientific articles to scientific journals. This PkM activity is carried out through lectures, demonstrations, and interactive discussions. The results of the training obtained are 1) the teacher gains basic knowledge about the preparation of scientific research articles, 2) the teacher is able to find and adjust the target of the intended scientific journal according to the focus and scope of the article that has been made, and 3) the teacher is able to carry out the article submission stages on scientific journals at the IAIN Ambon Journal House. Referring to the results of this PkM activity, the school should be more intensive in carrying out training activities, so that teachers will increase their capacity in writing and publishing scientific articles. Keywords. writing and publishing, scientific research articles, teacher, open journal system (OJS)